ANALYSIS OF PHYSICAL PREPARATION IN ORGANIZING QUICK COUNTERATTACKS IN 17–18-YEAR-OLD HANDBALL PLAYERS - Gulomjonovich, G‘ofurov Mirzohid (Research Focus International Scientific Journal, 2026)
It was considered appropriate to conduct a questionnaire survey to identify factors affecting the physical fitness of 17–18-year-old handball players in organizing quick counterattacks.